The Daily Relation between Parental Rejection and Emotional Eating in Youngsters: A Diary Study - Vandewalle, Julie; Mabbe, Elien; Debeuf, Taaike; Braet, Caroline; Moens, Ellen (Frontiers in Psychology, 2017)
Background: This study investigated the daily relation between parental rejection and peer rejection on the one hand and emotional eating in youngsters on the other hand. Methods: Participants (N = 55) between the ages of 11 and 15 years completed a 7-day diary. A multilevel design was used to examine day-to-day within-person relationships between parental and peer rejection (measured by CHS) and emotional eating (measured by DEBQ-C) of youngsters. Results: The results showed that daily variations in parental rejection were related to daily variations in emotional eating of the youngsters. Daily peer rejection was only marginally significantly related to the emotional eating of the youngsters. Conclusions: These results indicate that especially parental rejection, and to a lesser extent peer rejection, are associated with the emotional eating of youngsters. The findings highlight the importance of addressing the parent-child relationship in interventions for emotional eating in youngsters.